Evidence for ABL Amplification in Multiple Myeloma and Therapeutic Implications. (15th March 2022) - Huang, He; Zhou, Shuping; Lin, Hongdou; Guo, Wenjian; Lin, Ying; Yao, Ronxin; He, Licai; Yu, Kang; Li, Qian
Abstract : Background . Cytogenetic abnormalities are considered initiating events in the pathogenesis of multiple myeloma (MM) and are assumed to be of clinical significance. Methods . Fluorescence in situ hybridization (FISH) was used to analyze chromosomal architecture in 101 patients with MM. We evaluated overall patient survival and assessed the cytotoxicity of imatinib against MM cells using a CCK8 assay. Results . ABL gene amplification was detected in 67 patients (66.3%). However, ABL gene amplification was not associated with clinical features, cytogenetic abnormalities (c-Myc amplification, IGH rearrangement, RB1 deletion, p53 deletion, or 1q21 amplification), or overall survival. ABL amplification in MM cell lines (LP-1 and U266) was revealed by FISH. Furthermore, the ABL protein was easily detectable in MM cell lines and some tumor cells by western blotting. A CCK8 assay indicated limited cytotoxicity of imatinib against MM cells. Conclusions . Our study firstly discussed ABL gene amplification was prevalent in MM cells, and we believe that the ABL gene would potentially be a useful target in the treatment of combination strategy for MM with ABL amplification in the future.